Assessing Diabetes Risk Factors in Rural Dwelling Grandparent Caregivers. (June 2020) - Smalls, Brittany L.; Adegboyega, Adebola; Contreras, Omar A.; Palmer, Kelly; Hatcher, Jennifer
Objective: The purpose of this study is to assess type 2 diabetes mellitus (T2DM) risk factors in grandparent caregivers living in a rural environment. Methods: Clinical measures (hemoglobin A1c [HbA1c], blood pressure, and lipids) and self-reported data on social environment factors were attained. Data were analyzed via Pearson's correlation and regression models. Results: By clinical definition of diabetes (HbA1c ≥ 6.5%), 21% were prediabetic and 28% had undiagnosed T2DM. There was an association between the number of individuals in the home and triglycerides ( r = −.25), high-density lipoproteins (HDL; r = .43), and body mass index (BMI; r = .39). Guardianship status had a significant association with BMI ( r = −.38). There was a significant association between low-density lipoprotein (LDL; r = −.32) and access to community shared resources. In the adjusted linear model, the number of grandchildren in the home had a significant relationship with HDL (β = .012, p = .021) whereas the number of individuals living in the home had a statistically significant relationship with HDL (β = .026, p < .000) and BMI (β = .046, p = .02). In addition, 15% of participants reported being food insecure. Discussion: Efforts are needed to identify and screen at-risk populations living in geographically isolated areas. Considerations should be given to leveraging existing community resources for grandparent caregivers via schools, health systems, and government agencies to optimize health and well-being.